2019
DOI: 10.1038/s41598-019-48112-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aniseikonia and influencing-factors following successful macula-off retinal detachment surgery

Abstract: This study investigated the changes in the severity of aniseikonia after surgery for macula-off retinal detachment (RD), and the relationship between aniseikonia and retinal microstructures. The study included 26 eyes of 26 patients undergoing RD surgery. Visual acuity was measured preoperatively, and at 3, 6, and 12 months postoperatively. Degree of aniseikonia and OCT images were obtained at 3, 6, and 12 months postoperatively. The aniseikonia values (mean ± standard deviation) at 3, 6, and 12 months postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
0
18
4
Order By: Relevance
“…Micropsia was perceived by the majority of patients with aniseikonia, which confirms earlier findings. 6,13 However, the prevalence of aniseikonia in the current study was somewhat lower than in earlier studies. Okamoto et al 6 and Murakami et al 13 reported a prevalence of 61% and 58% in macula-off RRD patients.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Micropsia was perceived by the majority of patients with aniseikonia, which confirms earlier findings. 6,13 However, the prevalence of aniseikonia in the current study was somewhat lower than in earlier studies. Okamoto et al 6 and Murakami et al 13 reported a prevalence of 61% and 58% in macula-off RRD patients.…”
Section: Discussioncontrasting
confidence: 86%
“…6,13 However, the prevalence of aniseikonia in the current study was somewhat lower than in earlier studies. Okamoto et al 6 and Murakami et al 13 reported a prevalence of 61% and 58% in macula-off RRD patients. Both studies found abnormalities in patients with aniseikonia, which included subretinal fluid and macular hole.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“… 4 , 6 Patients often experience debilitating micropsia in the affected eye, even in cases with significant improvement in the final corrected distance visual acuity (CDVA) after surgery, which may affect depth perception and binocularity. 7 …”
mentioning
confidence: 99%
“…Several studies have demonstrated that the retinal outer segment layer is reduced by approximately 10% of normal width with complete loss of cone photoreceptor markers within 1 week after detachment, with significant changes to the ganglion cell layer. 7 , 8 Duration of the macular detachment, bullous configuration, and CDVA at presentation are several factors that correlate with final CDVA in macula-off detachments. 4 , 5 , 6 …”
mentioning
confidence: 99%